Implementasi Metode Uswah Hasanah pada Pembelajaran Jarak Jauh di MTs Al Azhar Tembongraja Salem Brebes - Samsudin, Agus; Suhartini, Andewi; Ahmad EQ, Nurwadjah (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
This study aims to find out how the implementation of the Uswah Hasanah method during Distance Learning because of the COVID-19 pandemic at MTs Al Azhar Tembongraja, Salem, Brebes. This research is qualitative research with an analytical descriptive method. Data collection techniques were carried out through interviews and literature. The subjects in this study were the principal, deputy head of the curriculum, deputy head of students, some teachers, and some students. Data analysis was carried out by selecting the data obtained and then collected for analysis and conclusions drawn. The findings in this study are that the implementation of the Uswah Hasanah Method during the PJJ of the COVID-19 pandemic, educators experienced various difficulties because there was almost no face-to-face during learning. Although there is no face-to-face, educators use social media in applying the uswah method, including by saying greetings in each learning session, being on time in starting the lesson schedule, greeting students, asking how students are, and praying for them to always be given health, giving rewards with words of congratulations for outstanding students and other motivational words and so on through social media groups. Keywords: distance learning, Uswah hasanah, COVID-19 Pandemic Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana implementasi metode uswah hasanah Pembelajaran Jarak Jauh (PJJ) pada masa pandemi COVID-19 di MTs Al Azhar Tembongraja, Salem, Brebes. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif analitik. Teknik pengumpulan data dilakukan melalui wawancara dan kepustakaan. Subjek dalam penelitian ini ialah kepala sekolah, waka kurikulum, waka kesiswaan, sebagian guru dan sebagian peserta didik. Analisis data dilakukan dengan memilih data yang diperoleh selanjutnya dikumpulkan untuk dianalisis dan diambil kesimpulan. Hasil temuan dalam penelitian ini adalah bahwa implementasi metode uswah hasanah dimasa PJJ pandemi COVID-19 ini pendidik mengalami berbagai kesulitan karena hampir tidak adanya tatap muka selama pembelajaran. Meskipun tidak ada tatap muka, pendidik memanfaatkan media sosial dalam menerapkan metode uswah hasanah di antaranya dengan cara mendahului mengucapkan salam dalam setiap sesi pembelajaran, tepat waktu dalam memulai jadwal pelajaran, menyapa peserta didik, menanyakan kabar peserta didik dan mendoakannya agar selalu di beri kesehatan, memberikan reward dengan kata-kata selamat bagi siswa yang berprestasi serta kata-kata motivasi lainnya dan lain sebagainya melalui grup media sosial.